New Urbanization of the Steppe. Astana: A Capital Called the Capital - Gawęcki, Marek (Studia Historiae Oeconomicae, 2013)
Relocating the capital of Kazakhstan from Almaty to Akmola (then renamed Astana) in 1997 has been the subject of an intense debate, particularly within media. The process of creating the new capital of Kazakhstan should consider the broader perspective of historical, political and ideological, social, climatic and geographical factors, and finally to put the matter in terms of architecture and urban planning. The author considers this very broad perspective, finally expressing the hope that the project of “the city of the future” analyzed in the article, will become a permanent part of the Kazakh reality.